Design of a FPGA-based digital reactivity meter for Dalat Nuclear Research Reactor - Vo, Van Tai; Nguyen, Van Kien; Nguyen, Nhi Dien; Le, Van Hiep (Nuclear Science and Technology, 2023)
This paper describes a digital reactivity meter module based on solving the inverse kinetics equations and the time behavior of the output pulse frequency from the amplifier, which is proportional to the power of the Dalat Nuclear Research Reactor (DNRR). The designed reactivity meter, which operates online with real-time calculation, was tested using the PGT-17R simulator signals in comparison with the existing imported module PNO-121R5 of the DNRR’s control and protection system. The experimental results show that the technical characteristics and functions of the two modules are equivalent.